Influences of graphite electrode on degradation induced by accelerated charging–discharging cycling in lithium-ion battery. (4th March 2018) - Jung, Eun Young; Park, Choon-Sang; Lee, Jae Cheol; Park, Jong-Bong; Suh, Kwang Jong; Hong, Tae Eun; Lee, Dong Ho; Chien, Sung-Il; Tae, Heung-Sik
ABSTRACT: To investigate the effects of degradation on the Li-ion battery (LIB) during fast charging–discharging under various ambient temperatures, the structural changes and elemental distributions were investigated on the graphite electrode between pristine and degradation (Cell capacity < 50%) samples in LIB under room temperature (RT, 25°C) and low temperature (LT, 0°C) ambient using scanning electron microscope (SEM), transmission electron microscope (TEM), and time of flight-secondary ion mass spectrometry (ToF-SIMS). We focused our studies on the structural changes and element distributions via cross-section image for graphite electrode, which were cycled during fast charging–discharging under RT and LT (0°C), respectively. The TEM results show that the surface of graphite in case of LT (0°C) was only changed to amorphous state with cracks on the surface (∼10 µm thickness) partially, whereas the graphite of RT was not changed. Also, ToF-SIMS results confirm that the inhomogeneously concentrated elements of Li, F, and P originated from LiPF6 electrolyte were observed on the graphite surface only in the case of LT (0°C). Our measurement results are expected to contribute to revealing the degradation mechanism during fast charging–discharging cycling under LT (0°C) ambient.